2015
DOI: 10.1152/ajplung.00241.2014
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal nicotinic exposure augments cardiorespiratory responses to activation of bronchopulmonary C-fibers

Abstract: Rat pups prenatally exposed to nicotine (PNE) present apneic (lethal ventilatory arrest) responses during severe hypoxia. To clarify whether these responses are of central origin, we tested PNE effects on ventilation and diaphragm electromyography (EMGdi) during hypoxia in conscious rat pups. PNE produced apnea (lethal ventilatory arrest) identical to EMGdi silencing during hypoxia, indicating a central origin of this apneic response. We further asked whether PNE would sensitize bronchopulmonary C-fibers (PCFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 68 publications
5
19
0
Order By: Relevance
“…PNE pretreatment was the same as previously reported (10). Briefly, adult female rats were randomly designated to receivesaline(n =7,Ctrl)andnicotine(n =9,PNE)via a miniosmotic pump (0.25 ml/h for 28 d) (Alza, Palo Alto, CA, USA).…”
Section: Pne Animal Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…PNE pretreatment was the same as previously reported (10). Briefly, adult female rats were randomly designated to receivesaline(n =7,Ctrl)andnicotine(n =9,PNE)via a miniosmotic pump (0.25 ml/h for 28 d) (Alza, Palo Alto, CA, USA).…”
Section: Pne Animal Preparationmentioning
confidence: 99%
“…We recently found that PNE-induced death immediately after severe bradycardia and apneas during acute hypoxic exposure in rat pups at postnatal day (P)11-P14 (9). Prior to death, PNE also induced a remarkably prolonged apneic response to stimulation of bronchopulmonary C fibers (PCFs) (10). Besides PCFs, the superior laryngeal nerve (SLN) innervating the larynx (11,12) plays an important role in causing central apnea and bradycardia (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PNE pretreatment was the same as previously reported (Zhuang et al , 2015). Briefly, the adult females were randomly designated to receive vehicle (n = 25) and nicotine (n = 44) respectively via a mini-osmotic pump (0.25 μL/hr for 28 days, Alza Corp., Palo Alto, CA).…”
Section: Methodsmentioning
confidence: 99%
“…, 2009; Stephan-Blanchard et al , 2013). Our recent study showed a plasticity of bronchopulmonary C-fibers (PCFs) in PNE rat pups (Zhuang et al , 2015). This plasticity is characterized by a remarkable prolongation of the apneic response and augmentation of pulmonary C-neural response to right atrial injection of capsaicin, a selective stimulant to PCFs.…”
Section: Introductionmentioning
confidence: 99%